Efeitos do pós-operatório mediato de cirurgia bariátrica na capacidade funcional e na composição corporal em obesos: proposta de treinamento físico com eletroestimulação de corpo inteiro - André, Larissa Delgado (Universidade Federal de São Carlos, 2018)
Obesity characterized as an increase of adipose tissue, has reached epidemic proportions in the world and may leads to some comorbidities. Bariatric surgery has been considered the most effective treatment, being gastric bypass the most prevalent technique, carrying in substantial weight loss and long-term maintenance. The restrictive and hypocaloric diets in the postoperative period may enhance weight loss. However, this associated to physical inactivity causes lean mass reduction, which may lead to unfavorable consequences in terms of functional performance and aerobic capacity, being important to understand the outcomes resulting from early bariatric surgery, as well as the importance of early rehabilitation strategy programs in these individuals. In this context, we proposed a project (Study I) entitled “Functional and systemic effects of whole body electrical stimulation in the bariatric surgery postoperative period: study protocol for a randomized controlled trial. Additionally, a second study (Study II) will be presented with purpose of evaluate functional impairments and loss of lean mass in the mediate postoperative period, entitled “Impact of early bariatric surgery period on functional capacity in obese individuals”. Thirty-one obese subjects, aged between 18 and 45 years, underwent Roux-en-Y gastric bypass bariatric surgery. The preoperative evaluations consisted in anthropometric variables, body composition, maximal cardiopulmonary exercise test and the 6MWT. Two to ten days after hospital discharge, the postoperative (PO) assessment was performed with the body composition measurement and the 6MWT application. The main findings were: (1) low functional capacity in obese patients compared with distance predicted (2) functional capacity decline, significance decrease in distance walked during 6MWT in the postoperative period, (3) decline in ventilatory and metabolic variables that were associated with a reduction in lean and body mass, and (4) a reduction in weight loss with a significant decrease in lean body mass in all segments of body. In conclusion the mediate postoperative period is associated to a reduction in body composition, especially lean mass and submaximal functional capacity impairment, emphasizing the importance of functional capacity assessments and early intervention strategies to increase and / or maintain muscle and cardiorespiratory capacities, to improve health condition of these individuals.
Effects of bariatric surgery postoperative period on functional capacity and body composition in obese patients: proposal of physical training with whole body electrical stimulation
Keywords: Obesidade; Capacidade funcional; Teste de caminhada de seis minutos; Composição corporal; Cirurgia bariátrica; Obesity; Functional capacity; Six minutes walking test; Body composition; Bariatric surgery; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL